2015
DOI: 10.2495/mpf150271
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of the slurry flow in pipelines and prediction of flow regimes

Abstract: Large scale numerical modelling of slurry flow in horizontal pipelines has been carried out. A combination of analytical and commercial CFD modelling, with Eulerian two-phase flow models, has been used in the present investigation. The modelling results are validated with well-documented experimental data and are found to be in good agreement. Flow regime maps were developed and pressure drops calculated for a wide range of flow rates, particle sizes and solid concentrations. It was observed that flow regime m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The extensive drop in the yield stress and the viscosity is observed with 30% mixing proportions to the fly ash slurry whereas the aforesaid parameters rapidly shoot up with 40% of mixing proportions at all solid concentrations. Afterwards, the CFD modeling of sand water slurry in a horizontal pipeline has been accomplished using Eulerian two-phase model by Swamy et al [20]. The simulated results are verified with experimental data and heterogeneous flow regimes are found for larger particle sizes.…”
Section: Introductionmentioning
confidence: 97%
“…The extensive drop in the yield stress and the viscosity is observed with 30% mixing proportions to the fly ash slurry whereas the aforesaid parameters rapidly shoot up with 40% of mixing proportions at all solid concentrations. Afterwards, the CFD modeling of sand water slurry in a horizontal pipeline has been accomplished using Eulerian two-phase model by Swamy et al [20]. The simulated results are verified with experimental data and heterogeneous flow regimes are found for larger particle sizes.…”
Section: Introductionmentioning
confidence: 97%
“…Velocity profiles of slurry flow in pipes are influenced by particle density [12], particle size [13], particle velocity, solids concentration [14], and distance from the tube wall. At the region near the tube wall, a higher velocity contributes to the intact “streaky” structure of flow in single-phase flow.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Although laboratory experiments can restore many application scenarios to obtain credible data, the high cost of equipment and a significant amount of time spent in the experimental process seriously hinder researchers' enthusiasm. Benefiting from the improvement of computer computing power and the advancement of simulation software, more and more researchers have confirmed that fluid computing software to simulate the flow of highly concentrated slurries in pipes is an effective alternative to traditional lab experiments (Chen et al, 2017;Wu et al, 2018;Lahiri and Ghanta, 2010;Swamy et al, 2015;Kiran et al, 2019).…”
Section: Introductionmentioning
confidence: 99%